Analysis of the drug prescription for obese patients in Moscow - V. S. Krysanova; M. V. Zhuravleva; I. S. Krysanov; V. Yu. Ermakova (Izdatelstvo OKI, 2020)
Objectives. Obesity is a chronic relapsing disease that requires long-term and lifelong treatment. The development of diseases associated with obesity may cause the additional need for prescribing drug therapy. The main aim was to analyze the structure of preferential drug prescriptions for patients with obesity for the period 2015-2018 in Moscow. Methods. A pharmacoepidemiological retrospective analysis of the structure of drug prescriptions for the period 2015-2018 in Moscow according to the chosen nosology - obesity (code ICD-10 - E66) was performed. The total number of patients receiving medications, the total number of prescribed prescriptions and packages were analyzed. The results are processed using the MS Excel 2013 package and are presented in the form of absolute values, shares (%). Results. For the period from 2015-2018 there is a 3.5-fold increase in the number of obese patients receiving preferential drugs - from 259 people up to 899 people. Over the entire analyzed period, there is a gradual increase in the proportion of drugs for the treatment of diabetes (from 43.1 to 51.6 %), mainly due to metformin, and for the treatment of the gastrointestinal tract (from 6.7 to 18.7 %). The total costs of drug therapy for obese patients over the analyzed period increased by 3.6 times. The largest share of the costs was attributed to drugs for the treatment of diabetes mellitus (from 38.1 to 62.5 %). Conclusions. Analysis can help to improve the system of rational distribution of financial resources for the drug provision of obese patients through the development of clinical and economic approaches that allow choosing the most effective and less costly approaches to providing medical care to patients.